Pengaruh Tingkat Kepercayaan,Literasi Keuangan Syariah dan Lokasi terhadap Minat Menjadi Nasabah di Bank Syari’ah dengan Religiusitas Sebagai Variabel Moderasi (Studi Kasus Masyarakat Kecamatan Sosa) - Siti Khoiriah Hasibuan; Nurbaiti Nurbaiti (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
AbstractThe purpose of this study was to see the effect of the level of trust, Islamic financial literacy and location on the intention to become a customer in an Islamic bank moderated by religiosity. This study uses a descriptive quantitative approach with the MRA test used to interact with the independent variables and the moderating variables used. The results of this study indicate that the level of trust can affect the intention to become a customer in an Islamic bank in the Sosa District community, Padang Lawas Regency because the significance value is 0.000 > 0.05, for the Islamic financial literacy variable it cannot influence the intention to become a customer because it has a significant value of 0.821, the location variable can significantly influence the intention to become a customer with a significance value of 0.000. Religiosity as a moderating variable is able to strengthen the level of trust and location in influencing the interest in becoming a customer at an Islamic bank in the people of Sosa District, Padang Lawas Regency. Keywords: Level of Trust, Islamic Financial Literacy, Location, Religiosity, Islamic Banks